A review of mathematical modeling of addiction regarding both (neuro-) psychological processes and the social contagion perspectives. (April 2022) - van den Ende, Maarten W.J.; Epskamp, Sacha; Lees, Michael H.; van der Maas, Han L.J.; Wiers, Reinout W.; Sloot, Peter M.A.
Highlights: We reviewed computational models of both (neuro-)psychological processes and social dynamics of addiction. Psychological and social computational models are both very promising in studying addiction, but also currently disjoint. We propose to combine social and psychological models to bring the field forward. Abstract: Addiction is a complex biopsychosocial phenomenon, impacted by biological predispositions, psychological processes, and the social environment. Using mathematical and computational models that allow for surrogative reasoning may be a promising avenue for gaining a deeper understanding of this complex behavior. This paper reviews and classifies a selection of formal models of addiction focusing on the intra- and inter-individual dynamics, i.e., (neuro) psychological models and social models. We find that these modeling approaches to addiction are too disjoint and argue that in order to unravel the complexities of biopsychosocial processes of addiction, models should integrate intra- and inter-individual factors.